2021
DOI: 10.3390/vaccines9070730
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Data on Post Market Safety Profiles of COVID 19 Vaccines in Rheumatic Diseases: Assessments on Various Vaccines in Use, Different Rheumatic Disease Subtypes, and Immunosuppressive Therapies: A Two-Centers Study

Abstract: An increased risk of developing severe infections has been evidenced in rheumatic disease (RD) patients, and anti-COVID-19 vaccination is strictly recommended for RD patients. However, up to now, no data are available on safety, immunogenicity and efficacy of COVID-19 vaccinations in RD patients. The possible development of adverse events (AEs), including the flare-up of underlying RD, represents a matter of growing importance. The aim of our study is to assess, in RD patients, the safety profile of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 25 publications
(36 reference statements)
5
32
0
1
Order By: Relevance
“…On the other hand, several trials have reported on the safety of vaccines, and the association between disease flare and vaccination has also been an important issue. Recent preliminary data on post-market safety profile indicated that vaccines against COVID-19 do not necessarily exacerbate disease activity in rheumatic diseases [2]. Although the rapid development of vaccines has raised concerns regarding disease flare, the data reported so far are reassuring as far as the possibility of vaccine-related flares is concerned.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several trials have reported on the safety of vaccines, and the association between disease flare and vaccination has also been an important issue. Recent preliminary data on post-market safety profile indicated that vaccines against COVID-19 do not necessarily exacerbate disease activity in rheumatic diseases [2]. Although the rapid development of vaccines has raised concerns regarding disease flare, the data reported so far are reassuring as far as the possibility of vaccine-related flares is concerned.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of data on the immunogenicity and safety of vaccines in patients with autoimmune diseases is progressively increasing. 1 , 2 , 3 However, some concerns have been raised regarding the safety of the vaccines in patients with antiphospholipid antibodies, as these antibodies have been reported to appear following both infection and vaccination and have been identified in patients with COVID-19. 4 Although a few cases of thrombocytopenia and thrombotic events with clinical features resembling antiphospholipid syndrome have been reported in recipients of either adenoviral vector-based or mRNA-based COVID-19 vaccines, 5 a pathogenic link and, more critically, the clinical relevance of antiphospholipid antibodies in these clinical settings have yet to be fully elucidated.…”
mentioning
confidence: 99%
“…Concerning the possibility of inducing or enhancing the autoimmune response through molecular mimicry between the viral antigen and host antigen, Rotondo et al showed a low rate (5.7%) of disease relapse of IMRD after the first dose of vaccine, the rate of disease flare-up observed after BNT162b2mRNA/Pfizer vaccination could be due to the higher frequency of this vaccine administration. However, no significant differences in adverse events (AEs) between BNT162b2mRNA/Pfizer and ChAdOx1 nCoV19 were found in this study [ 51 ]. Watad et al reported that the average time between vaccination and new-onset or flare of symptoms was four days (median of 4 days [1–25 days] in those who developed an IMRD after the first dose and a median of 4 days [1–7 days] in those after the second dose) with most cases occurring after the first inoculation (77.8%) [ 52 ].…”
Section: Methodsmentioning
confidence: 81%
“…All four COVID-19 vaccines approved in Brazil are non-live, and thus, there is no risk of inducing vaccine-related disease [ 51 , 52 ]. Several studies confirmed that other non-live vaccines, such as those against influenza, pneumococcus, hepatitis A, hepatitis B, and human papillomavirus, are effective and safe for this population [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%